Pemodelan Decision Support System dalam Pemilihan Rumah Hunian Menggunakan Kombinasi Metode S.A.W. dan Fuzzy Logic - Candra Gudiato; Christian Cahyaningtyas; Noviyanti P. (G-Tech: Jurnal Teknologi Terapan, 2024)
The decision to choose a residential house is an important decision that has a long-term impact, so it requires careful and objective consideration. S.A.W. Method (Simple Addictive Weighting) and Fuzzy Mamdani are two methods that can be used to evaluate alternative residential homes based on the weights and values of specified criteria. By combining these two methods, it is hoped that the Decision Support System (DSS) can provide recommendations for the best residential houses according to user preferences. By using the S.A.W method, there are three important factors that need to be considered, namely house price, house location and land area. These three factors are then analyzed again to produce decisions or recommendations regarding the choice of residential house using the Fuzzy Mamdani method. The Fuzzy Mamdani method calculation produces a value of 50 which is tested using the Matlab application showing the same value, namely 50. From these results, it can be concluded that the S.A.W and Fuzzy Logic Mamdani methods are effective and accurate in selecting residential houses.